2016
DOI: 10.1007/s00726-016-2186-3
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of tryptophan analogues into the lantibiotic nisin

Abstract: Lantibiotics are posttranslationally modified peptides with efficient inhibitory activity against various Gram-positive bacteria. In addition to the original modifications, incorporation of non-canonical amino acids can render new properties and functions to lantibiotics. Nisin is the most studied lantibiotic and contains no tryptophan residues. In this study, a system was constructed to incorporate tryptophan analogues into nisin, which included the modification machinery (NisBTC) and the overexpression of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 37 publications
3
48
0
Order By: Relevance
“…3 ). This assumption is supported by mutational studies that showed a twofold activity reduction upon replacing I1 by a tryptophan 55 .…”
Section: Discussionmentioning
confidence: 83%
“…3 ). This assumption is supported by mutational studies that showed a twofold activity reduction upon replacing I1 by a tryptophan 55 .…”
Section: Discussionmentioning
confidence: 83%
“…The promiscuity of NisBTC and the development of an efficient production system for the modification and export of modified peptides enabled the production of putative lantibiotics from diverse bacteria in L. lactis (Majchrzykiewicz et al, 2010 ; van Heel et al, 2016 ). Moreover, this production system can be extended with additional enzyme modules (i.e., additional modification enzymes found in lantibiotic gene clusters) (van Heel et al, 2013 ) or with non-canonical amino acids (Zhou et al, 2016 ; Baumann et al, 2017 ; Zambaldo et al, 2017 ) that increase the repertoire of unusual amino acids that can be incorporated in vivo in peptides. These findings highlight the large potential of using Synthetic Biology principles in the production of novel lanthipeptides (for a review see Montalbán-López et al, 2012 , 2017 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…18-19 Kuipers also reported the incorporation of tryptophan analogues into Nisin using an auxotrophic strain. 20 With the goal of creating Nisin variants through biomimetic cyclization reactions (Figure 2), we built upon the former system 18 and began by recombinantly expressing wild type (WT) NisA in bacterial strains in which we have previously genetically encoded a large number of ncAAs. The nisA structural gene together with the dehydratase ( nisB ), were inserted into a pRSF-1 vector to afford pRSF-NisA.…”
mentioning
confidence: 99%